ANALISIS PERILAKU KONSUMSI DI LINGKUNGAN KELUARGA PADA SISWA KELAS VIII SMPN 1 BATU AMPAR KABUPATEN KUBU RAYA - Asmani Asmani; Sulistyarini Sulistyarini; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The purpose of this research was to determine consumption behavior in the family environment to the tenth grade of students SMPN 1 Batu Ampar, Kubu Raya Regency. The problems in this research were: 1) How is the process making consumption decisions in the family environment to the tenth grade of students SMPN 1 Batu Ampar, Kubu Ray Regencyt?. 2) What are the factors which affects consumption behavior in the family environment in students class VIII SMPN 1 Batu Ampar, Kubu Raya Regency?. Research result showed that consumption behavior in the inner family environment the decisionmaking process tends to lead irrationally, this was seen from the recognition of needs, search information,evaluation of alternatives before purchase, purchasing decisions, and post-purchase behavior. As for the factors that influence consumption behavior in the family environment, there were: 1) internal factors, motivation, personality, and lifestyle. 2) external factors, culture, family, and reference group. Keywords: Consumption Behavior, Family Environment